Puddles, parties and professors: linking word categorization to neural patterns of visuospatial coding - Quadflieg, S. (2011)
Behavioral evidence suggests that during word processing people spontaneously map object, valence, and power information to locations in vertical space. Specifically, whereas "overhead" (e. g., attic), positive (e. g., party), and powerful nouns (e. g., professor) are associated with "up," "underfoot" (e. g., carpet), negative (e. g., accident), and powerless nouns (e. g., assistant) are associated with "down." What has yet to be elucidated, however, is the precise nature of these effects. To explore this issue, an fMRI experiment was undertaken, during which participants were required to categorize the position in which geometrical shapes appeared on a computer screen (i.e., upper or lower part of the display). In addition, they also judged a series of words with regard to location (i.e., up vs. down), valence (i.e., good vs. bad), and power (i.e., powerful vs. powerless). Using multivoxel pattern analysis, it was found that classifiers that successfully distinguished between the positions of shapes in subregions of the inferior parietal lobe also provided discriminatory information to separate location and valence, but not power word judgments. Correlational analyses further revealed that, for location words, pattern transfer was more successful the stronger was participants' propensity to use visual imagery. These findings indicate that visual coding and conceptual processing can elicit common representations of verticality but that divergent mechanisms may support the reported effects.